Aridity drove the evolution of extreme embolism resistance and the radiation of conifer genus Callitris. Issue 1 (5th April 2017) - Larter, Maximilian; Pfautsch, Sebastian; Domec, Jean‐Christophe; Trueba, Santiago; Nagalingum, Nathalie; Delzon, Sylvain
Summary: Xylem vulnerability to embolism is emerging as a major factor in drought‐induced tree mortality events across the globe. However, we lack understanding of how and to what extent climate has shaped vascular properties or functions. We investigated the evolution of xylem hydraulic function and diversification patterns in Australia's most successful gymnosperm clade, Callitris, the world's most drought‐resistant conifers. For all 23 species in this group, we measured embolism resistance ( P 50 ), xylem specific hydraulic conductivity ( K s ), wood density, and tracheary element size from natural populations. We investigated whether hydraulic traits variation linked with climate and the diversification of this clade using a time‐calibrated phylogeny. Embolism resistance varied widely across the Callitris clade ( P 50 : −3.8 to −18.8 MPa), and was significantly related to water scarcity, as was tracheid diameter. We found no evidence of a safety‐efficiency tradeoff; K s and wood density were not related to rainfall. Callitris diversification coincides with the onset of aridity in Australia since the early Oligocene. Our results highlight the evolutionary lability of xylem traits with climate, and the leading role of aridity in the diversification of conifers. The uncoupling of safety from other xylem functions allowed Callitris to evolve extreme embolism resistance and diversify into xeric environments. Abstract : See also the Commentary on this article byBrodribb, 215 : 9–11 .